Soft Tissue Reconstruction in the Extremities: Principles, Techniques, and Outcomes - Lee, Che-Hsiung; Chen, Shih-Heng (Seminars in Plastic Surgery, 2025)
Soft tissue reconstruction in the extremities is complicated by the fact that injuries often involve composite defects of skin, muscle, tendon, nerve, and bone. In both the upper and lower limbs, achieving reliable soft tissue coverage, restoring function, and reducing complications are critical goals. The upper extremity requires precision and fine manipulation, whereas the lower limb should be reconstructed to support weight-bearing and mobility. Free flaps have become a routine part of the surgical armamentarium, offering flexible solutions tailored to different needs. Donor sites in the lower extremities are favored due to the availability of high-quality tissue, minimal visible scarring, and the possibility of a two-team approach. Careful planning not only improves wound healing but also accelerates rehabilitation and reduces the need for revision surgeries, underscoring the importance of flap choice, anatomical knowledge, and surgical skill.
Keywords: soft tissue coverage; extremity reconstruction; free flaps; functional restoration